Advances in tilt control design of high-speed railway vehicles: a study on fuzzy control methods - Zamzuri, Hairi (ICIC International, 2012)
The advantage of high speed trains is in the reductiot: of jo'urrtey times between two places. Most countries developed new infrastruct'ure to accommodate the need for high speed trains. However, this approach is rather costly. An alternative solution, which avoids new infrastruct'ure costs and merely increases maintenance cost of current rail tracks, is to introduc« tilting train technology. The main idea is tilting the vehicle body while on curced sections of the rail track. Current technologies in tilting railway vehicles 'use a 'precedence' control scheme; however, this increases comple'J:ity on the act'ual controller structure and inter-vehicle signal connections. Heseorcb. on local sensor loop control strategies is still important to oocrcome sucl: drawbacks. lVork 'using conventional and modern control approaches has been investigated by preoious researchers, In this paper, we propose a fuzzy correction mechanism acting as 'add-on' to enhance the capability of the controller response on c'urued track untlunit. compromising the effect from track irrcquluritie» on the vehicle. The fuzzy correction mechanism, as it is referred to, is applied in series with the nominal controller. Furthermore, the proposed control scheme is compared with a precedence type controller and a classical type controller to iliustrat« its effectiveness.